Advanced engineering analysis - Dukkipati, Rao V. (Alpha Science International, 2006)
This book discusses the theories, principles and methods on vector and vector spaces, linear algebra, Laplace transform, Fourier series and integrals, fourier transforms, vector differential calculus, vector integral calculus and partial differential equations and boundary value problem